Overtaking Assistant System Based on Fuzzy Logic - Noor Cholis Basjaruddin; Kuspriyanto Kuspriyanto; Didin Saefudin; Edi Rakhman; Adin Mochammad Ramadlan (Universitas Ahmad Dahlan, 2015)
Safety and comfort are two important aspects which must be achieved at the time of driving.The level of safety in driving can be improved by reducing driver (human) error. An auxiliary device is required by the driver to avoid an accident. Advanced Driver Assistance Systems (ADASs) are systems to help the driver in the driving process. Overtaking Assistance System (OAS) is the subsystem of ADAS that functions to assist the driver in overtaking process. This paper presents decision-making system based on fuzzy logic for OAS. Inputs of decision-making system are the distance of ego vehicle and a vehicle that will be overtake as well as the distance ego vehicle and the vehicle on the other lane. Decisions of a decision-making system are vehicle doing approaching, tailgating, and overtaking. The result from hardware simulation that using remote control car shows that the decision-making system algorithm can work according to the design.